Balance of care activity after EMA recommendation for DPYD gene testing in Galicia - Gil-Rodríguez, Almudena; Recarey-Rama, Sheila; Rodríguez-Viyuela, Ana; Barros, Francisco; Carracedo, Angel; Maroñas, Olalla (Frontiers in Pharmacology, 2025)
IntroductionSince April 2020, pretherapeutic screening for accessing the deficiency of the DPD enzyme by genotyping the dihydropyrimidine dehydrogenase gene (DPYD) is required by the European Medicine Agency (EMA) prior to the administration of fluoropyrimidine-based chemotherapy. In May 2020, the Spanish Drug and Medical Devices Agency (AEMPS) published an informative note highlighting the importance of DPYD analysis prior fluoropyrimidines derivatives administration to prevent the development of severe adverse drug reactions (ADRs). The publication of these recommendations marked a turning point in the daily routine in many pharmacogenetics laboratories in Spain. This article aims to illustrate the current state of the DPYD testing in the reference genomic medicine center in Galicia, 4 years after the EMA’s updated recommendations.MethodsThe Pharmacogenetics Unit in the reference genomic medicine center conducted genotyping of the four DPYD variants recommended by regulatory agencies that oncologists can adjust fluoropyrimidine treatment based on DPYD genotype results.ResultsBetween 1 June 2020 to 1 May 2024, both included, a total of 2,798 DPYD requests were analyzed. DPYD genotyping results revealed a 3.15% prevalence of heterozygosity for at least one of the four DPYD variants, being rs56038477 the most prevalent variant (1.31%).ConclusionThis study addresses the importance of the DPYD analysis implementation in clinical practice after the changes in EMA and AEMPs recommendations which has led to a significant increase in DPYD genotyping requests. This highlights the significance of preemptive genotyping for accurately adjusting fluoropyrimidines doses before initiating treatment.